A universal gelation strategy of bivalent anions to construct nanofibrous lysozyme hydrogels for immunomemory anti‐recurrence of diabetic wound infection by activating the cGAS‐STING pathway - Aihui Wang; Liqun Li; Liqian Zheng; Bang‐Ping Jiang; Yihao Liu; Rimei Huang; Huimin Qiu; Shichen Ji; Hong Liang; Xing‐Can Shen (Aggregate)
Abstract Antibacterial lysozyme hydrogels show attractive advantages in wound dressings due to their intrinsic antibacterial activity and excellent biochemical and mechanical properties. Unfortunately, the development of such hydrogels is still greatly limited due to the lack of universal gelation strategies. Herein, a universal gelation strategy between lysozyme‐nanofiber (LZF) and inorganic salts is proposed for the first time to construct functional nanofibrous lysozyme‐based hydrogels. In particular, divalent anions are found to universally drive LZF for the aggregation and transformation into three‐dimensional nanofibrous network hydrogels via electrostatic interaction, and the key role of divalent anions in the gelation is further proved by molecular dynamics simulation. In addition, near‐infrared light‐mediated photothermal characteristics are endowed with LZF to enhance its inhibitory activity of multidrug‐resistant bacteria by the skeleton modification with genipin to produce genipin‐conjuagted LZF (GLZF). As a distinct application paradigm, the brilliant immunomemory MnSO4‐crosslinked GLZF hydrogel is constructed to sensitize the cGAS‐STING pathway and skillfully establish an antibacterial immune microenvironment. It can excellently realize the anti‐recurrence of diabetic wound infection via photo‐enhanced bacterial killing and the cGAS‐STING pathway. Thereby, it paves the way to employ the universal divalent anion‐mediated gelation strategy for the future development of functional inorganic salt hybrid lysozyme hydrogels.